Reverse Electrodialysis: Potential Reduction in Energy and Emissions of Desalination - Carolina Tristán; Marcos Fallanza; Raquel Ibáñez; Inmaculada Ortiz (Applied Sciences, 2020)
Salinity gradient energy harvesting by reverse electrodialysis (RED) is a promising renewable source to decarbonize desalination. This work surveys the potential reduction in energy consumption and carbon emissions gained from RED integration in 20 medium-to-large-sized seawater reverse osmosis (SWRO) desalination plants spread worldwide. Using the validated RED system’s model from our research group, we quantified the grid mix share of the SWRO plant’s total energy demand and total emissions RED would abate (i) in its current state of development and (ii) if captured all salinity gradient exergy (SGE). Results indicate that more saline and warmer SWRO brines enhance RED’s net power density, yet source availability may restrain specific energy supply. If all SGE were harnessed, RED could supply ~40% of total desalination plants’ energy demand almost in all locations, yet energy conversion irreversibility and untapped SGE decline it to ~10%. RED integration in the most emission-intensive SWRO plants could relieve up to 1.95 kg CO2-eq m−3. Findings reveal that RED energy recovery from SWRO concentrate effluents could bring desalination sector sizeable energy and emissions savings provided future advancements bring RED technology closer to its thermodynamic limit.